The purpose of knowledge: pragmatism and the praxis of marxist criminology - O'Malley, Pat (Contemporary crises, 1988)
This paper revives and revises the argument that there is no place for a concept of crime in marxist theory, and consequently that there is no theoretical justification for the development of marxist criminology. However, earlier essays along these lines have adopted a rationalist epistemology in advancing this case - with its attendant difficulties of idealism, privileged conceptualization and inflexibility. The present paper attempts to escape such problems, and to extend the critique of criminological theorization, by developing its case on the basis of a pragmatist epistemology. It is argued that the conflicting aims of marxist theory and the bourgeois legal theory from which ‘crime’ is transferred make it difficult for marxist criminology to generate a unified theory to guide political practice and research. Moreover, Marxists' privileging of the concept of crime may be systematically blinding them to political developments which render criminology historically obsolescent.